Anaerobic co-digestion of khat waste and cow dung for enhanced bio-methane production potential: Substrates conversion rate - Henok Akililu Legesse; Wagene Hailu Debele; Akiber Chufo Wachemo (Heliyon)
Anaerobic digestion technology is one of the most paramount eco-friendly wastes to energy conversion processes. This study was conducted to characterize the physicochemical properties of khat and Cow dung along with examining the bio-methane production potential and substrate conversion rate of feedstock through seven triplicate proportions of laboratory scale batch anaerobic reactors for a 27 days digestion period under mesophilic conditions. The maximum and minimum bio-methane yield of 283.52 ± 7.17 CH4 mL/g VS and 142.83 ± 3.56 CH4 mL/g VS were generated from the digester, with the higher proportion of Khat waste in the T-5 (2:1) and the sole substrate anaerobic digestion of Cow dung in T-7 (0:1) respectively. The conversion rates of cellulose and hemicellulose components from Khat waste were 44.4 and 47.2 %, respectively. The result demonstrates that the anaerobic co-digestion of khat waste and cow dung plays a critical role in enhanced biomethane production due to effective synergism.